Effects of calcimimetics on long-term outcomes in dialysis patients: literature review and Bayesian meta-analysis. (15th May 2018) - Lozano-Ortega, Greta; Waser, Nathalie; Bensink, Mark E; Goring, Sarah; Bennett, Heather; Block, Geoffrey A; Chertow, Glenn M; Trotman, Marie-Louise; Cooper, Kerry; Levy, Adrian R; Belozeroff, Vasily
Aim: Randomized controlled trials (RCTs) with clinical outcomes are considered the gold standard for regulatory approval. However, by design they are only able to answer a small number of clinical questions. Other high-quality studies are required for clinical decision-making. The EVOLVE was the largest RCT, evaluating the effects of cinacalcet on clinical outcomes among adult patients receiving maintenance dialysis suffering from secondary hyperparathyroidism. While the EVOLVE trial did not reach its primary end point, imbalance in subjects' age at randomization and discontinuation rates are two of the reasons that the lack of mortality benefit is in question. We undertook a systematic literature review and Bayesian meta-analysis combining randomized and observational studies on the estimated effects of the oral calcimimetic cinacalcet on clinical outcomes including all-cause mortality, cardiovascular-related mortality, hospitalization for cardiovascular events, fracture and parathyroidectomy among patients on maintenance dialysis.Methods: Data sources included MEDLINE, EMBASE and Cochrane Central Register of Controlled Trials databases. RCTs and observational studies were included. Data extraction was completed by two authors independently and in duplicate determined the methodological quality of the studies and extracted data.Results: Of 564 unique citations identified, 16 studies were included: six observational studies and ten RCTs. Four high-quality studies (two observational and two RCTs) were deemed suitable for meta-analysis. Results indicated a statistically significant reduction in the risk of death associated with cinacalcet (hazard ratio: 0.83; 95% credible interval: 0.78–0.89).Conclusion: The results of this meta-analysis indicate that treatment of secondary hyperparathyroidism with calcimimetic therapy may in fact reduce mortality among patients receiving maintenance dialysis. This finding provides justification for a well-designed and adequately powered randomized trial to definitively address the question.